2010
DOI: 10.1186/1752-0509-4-101
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-time modeling of cell fate determination in Arabidopsis flowers

Abstract: BackgroundThe genetic control of floral organ specification is currently being investigated by various approaches, both experimentally and through modeling. Models and simulations have mostly involved boolean or related methods, and so far a quantitative, continuous-time approach has not been explored.ResultsWe propose an ordinary differential equation (ODE) model that describes the gene expression dynamics of a gene regulatory network that controls floral organ formation in the model plant Arabidopsis thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…Advanced proteomics and in vivo imaging approaches can be used to systematically study the regulation of MADS-box transcription factor activities in planta. In addition, the modeling of MADS-box regulatory networks can provide novel insights (Espinosa-Soto et al, 2004;van Mourik et al, 2010), but will require more quantitative in vivo data in the future.Finally, a number of studies have shown that many MADS-box genes have roles in more than one organ or developmental stage. How can the same factor have different functions in different developmental contexts?…”
mentioning
confidence: 99%
“…Advanced proteomics and in vivo imaging approaches can be used to systematically study the regulation of MADS-box transcription factor activities in planta. In addition, the modeling of MADS-box regulatory networks can provide novel insights (Espinosa-Soto et al, 2004;van Mourik et al, 2010), but will require more quantitative in vivo data in the future.Finally, a number of studies have shown that many MADS-box genes have roles in more than one organ or developmental stage. How can the same factor have different functions in different developmental contexts?…”
mentioning
confidence: 99%
“…2 The interacting MADS genes form a gene regulatory network that has been studied previously with the help of mathematical modeling. [3][4][5] Recently, Urbanus et The resulting computational model will help explore hypothetical interactions between the MADS and auxin regulation networks in floral organ patterning. For example, it is still unknown whether MADS proteins function mainly in dimers, 8 or in tetramers, or even higher order complexes.…”
Section: Integrating Two Patterning Processes In the Flowermentioning
confidence: 99%
“…For instance, the auxin signaling model by Vernoux et al (2011) reduces the binding of TIR1 receptors with auxin and Aux/IAA to a simple MichaelisMenten term in the equations (Figure 2A) by assuming this processes is fast when compared with changes in gene expression. This type of reduction is also often used to eliminate the variables describing dimers from a system, assuming proteinprotein binding is much faster than the processes such as transcription or translation (for example, see Savage et al, 2008;van Mourik et al, 2010;Band et al, 2012c). However, it is worth stressing that the quasi-steady state assumption can lead to the wrong dynamics if this assumption is not valid (i.e., if there is not a clear separation of timescales).…”
Section: How To Build and Analyze Small Networkmentioning
confidence: 99%
“…Organisms such as Arabidopsis typically have large gene families in their genome (such as the 29 Aux/IAAs and 23 ARFs; Chapman and Estelle, 2009), and it is common for modelers to try and reduce this complexity by lumping whole gene families together so that they are represented by a single variable (for example, see Middleton et al, 2010;van Mourik et al, 2010). This is a reasonable first step and is most likely a valid one provided the individual family members all have similar behavior.…”
Section: How To Build and Analyze Small Networkmentioning
confidence: 99%
See 1 more Smart Citation